Photosensitized generation of singlet oxygen from (substituted bipyridine)ruthenium(II) complexes - Abdel-Shafi, A; Beer, P; Mortimer, R; Wilkinson, F (2001)
Photophysical properties in dilute MeCN solution are reported for seven Ru11 complexes containing two 2,2′-bipyridine (bpy) ligands and different third ligands, six of which contain a variety of 4,4′-carboxamide-disubstituted 2,2′-bipyridines, for one complex containing no 2,2′-bipyridine, but 2 of these different ligands, for three multinuclear Ru11 complexes containing 2 or 4 [Ru(bpy)2] moieties and also coordinated via 4,4′-carboxamide-disubstituted 2,2′-bipyridine ligands, and for the complex [(Ru(bpy)2(L)]2+ where L is N,N′-([2,2′-bipyridine]-4,4′-diyl)bis[3- methoxypropanamide]. Absorption maxima are red-shifted with respect to [Ru(bpy)3]2+, as are phosphorescence maxima which vary from 622 to 656 nm. The lifetimes of the lowest excited triplet metal-to-ligand charge transfer states 3MLCT in de-aerated MeCN are equal to or longer than for [Ru(bpy)3]2+ and vary considerably, i.e., from 0.86 to 1.71 μs. Rate constants kq for quenching by O2 of the 3MLCT states were measured and found to be well below diffusion-controlled, ranging from 1.2 to 2.0.109 dm3 mol-1 s-1. The efficiencies fΔT of singlet-oxygen formation during oxygen quenching of these 3MLCT states are relatively high, namely 0.53-0.89. The product of kq and fΔT gives the net rate constant kq1 for quenching due to energy transfer to produce singlet oxygen, and kq - kq1 equals kq3, the net rate constant for quenching due to energy dissipation of the excited 3MLCT states without energy transfer. The quenching rate constants were both found to correlate with ΔGCT, the free-energy change for charge transfer from the excited Ru complex to oxygen, and the relative and absolute values of these rate constants are discussed.